Reasons in favour of universal vaccination campaign against COVID-19 in the pediatric population - Nicola Principi; Susanna Esposito (BMC, 2022)
Abstract Background Despite the growing evidence of the extreme efficacy of COVID-19 vaccines in adults and the elderly, the administration of the same prophylactic measures to pediatric subjects is debated by some parents and by a number of researchers. The aim of this manuscript is to explain the reasons for overcoming hesitancy towards COVID-19 vaccination in children and adolescents and to highlight the importance of universal COVID-19 vaccination in the pediatric population. Main findings Recent epidemiological data suggest that the risk that a child with COVID-19 is hospitalized or admitted to the pediatric intensive care unit is greater than initially thought. Children may also suffer from long COVID and school closure because of COVID-19 can cause relevant mental health problems in the pediatric population. Placebo-controlled, observer-blinded, clinical trials showed appropriate efficacy, safety and tolerability of authorized mRNA COVID-19 vaccines in children and adolescents 12-17 years old. Vaccination in children younger than 12 years of age will allow further benefits . Conclusions COVID-19 vaccine administration seems mandatory in all the children and adolescents because of COVID-19 related complications as well as the efficacy, safety and tolerability of COVID-19 vaccines in this population. Due to the recent approval of COVID-9 vaccines for children 5-10 years old, it is desirable that vaccine opponents can understand how important is the universal immunization against COVID-19 for the pediatric subjects.